Formation control and coordination for multiple robots guided by camera - Nguyen Minh, Hoang (2016)
Man-made multi-robot systems (e.g., intelligent robot networks or a group of networked intelligent roots) have been advancing apace with the help of high-performance hardware and computational technologies. Examples of such systems include teams of smart cars, autonomous robots, robot soccer players, and unmanned micro airplanes. However, despite the high-performance computing, communication, sensing, and power devices used in these systems, their effectiveness in uncertain environments appears to still fall behind the natural systems such as a swarm of ants or a flock of birds. This project aims at improving a multi-robot test platform by designing and implementing intelligent control strategies. The main objective of this project is to put the robots under some kinds of formation when moving or when accomplishing the task in different enviroment. In order to do so, all robots must be able to exchange information about their position, moving direction and speed to the main controller or to each other (if they can be put in automation mode). So that the user do not have to control each robot seperately but can select any robot to be the lead to indirectly manipulate the other robots